CORONARY COLLATERAL CIRCULATION IN INFARCTION-RELATED ARTERY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH RISE AND WITHOUT RISE OF ST SEGMENT - N. A. Yaitsky; O. G. Zverev; A. B. Volkov; A. V. Voinov; R. I. Abdulragimov (Вестник хирургии имени И.И. Грекова, 2018)
The authors analyzed a condition of coronary collateral circulation in infarction-related artery in patients with acute myocardial infarction with rise and without rise of ST segment. The assessment of collateral circulation was made by coronary angiography using Rentop scale. Results of the research showed, that collateral circulation wasn’t visualized by angiography in the first hours after acute myocardial infarction with the rise of ST segment. Apparently, this circulation didn’t significantly assisted in maintenance of vital capacity of the myocardium in the pool of infarction-related occlusive coronary artery. Visualization of collateral circulation was noted in majority of patients with acute myocardial infarction without the rise of ST segment. Collateral flow was an important alternative source of blood supply of the heart in patients without rise of ST segment in the period of critical reduction of the antegrade blood flow.